Effect of temperature on the kinetics of electrochemical insertion of li-ions into a graphite electrode studied by kinetic Monte Carlo - Gavilán Arriazu, Edgardo Maximiliano (2019)
The effect of temperature on the kinetics of electrochemical insertion/removal of lithium in graphite is analyzed by kinetic Monte Carlo methods. Different electrochemical techniques are simulated at different temperatures and responses are compared with experimental results. Simulated voltammograms show, similarly to experiment, how the behavior of the system becomes closer to equilibrium as temperature increases. Calculated chronoamperometric profiles show a different qualitative behavior in the current at different temperatures, especially in the Cottrell representation peaks, explained in terms of the relative importance of diffusive versus charge transfer processes at different temperatures. Results at room temperature are in good agreement with experiment, and we further evaluate trends at elevated temperature that have not yet been described in experimental or theoretical works. Exchange current densities for different degrees of lithium intercalation at different temperatures are predicted using potentiostatic simulations, showing an Arrhenius-type relationship. The dependence of the exchange current on electrolyte composition is simulated by investigating the effect of different activation energy barriers at different temperatures. The influence of temperature on diffusion coefficients as a function of lithiation fraction in graphite is simulated and related to Arrhenius plots, explaining the experimentally observed changes in diffusion phenomena with lithium composition and temperature.